2014
DOI: 10.1109/tasc.2013.2287756
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Heat Treatment and Epoxy Impregnation of a Large <formula formulatype="inline"> <tex Notation="TeX">$\hbox{Nb}_{3}\hbox{Sn}$</tex></formula> CICC Coil for a Series-Connected Hybrid Magnet

Abstract: Recent activities that were conducted on the Helmholtz Zentrum Berlin Series-Connected Hybrid outsert coil included the reaction heat treatment and vacuum-pressure impregnation. A thermocouple was wound into the windings for diagnostic purposes during processing of the coil. To maintain a reasonable temperature differential across the coil, the ramp rate was limited to approximately 2.7 • C/hr. Epoxy impregnation was conducted with an epoxy developed in-house. The epoxy is transferred in vacuum but cured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…by a copper sleeve, to prevent corrosion by oxygen. The thermal gradients, which typically occur for heat treatments of heavy coils [67], remain an unsolved challenge for large Bi2212 magnets. The shrink age by 4.2% of the Bi2212 wires during the overpressure heat treatment [68] is another reason of concern for the use of Bi2212 wires in a CICC: after heat treatment the cable will be loose in the conduit and may move under the Lorenz forces leading to instability and/or mechanical damage at bending.…”
Section: Magnet Technology For Htsmentioning
confidence: 99%
“…by a copper sleeve, to prevent corrosion by oxygen. The thermal gradients, which typically occur for heat treatments of heavy coils [67], remain an unsolved challenge for large Bi2212 magnets. The shrink age by 4.2% of the Bi2212 wires during the overpressure heat treatment [68] is another reason of concern for the use of Bi2212 wires in a CICC: after heat treatment the cable will be loose in the conduit and may move under the Lorenz forces leading to instability and/or mechanical damage at bending.…”
Section: Magnet Technology For Htsmentioning
confidence: 99%
“…A concern during heat treatment is getting the core of the windings to the reaction temperature fast enough without over reacting the outer coil regions. To reduce the delay, an overshoot in the high temperature plateau was performed, in a similar manner as was done with the SCH outsert coils [10]. Fig.…”
Section: Reaction Heat Treatmentmentioning
confidence: 99%
“…A large variability in the RRR was also measured for the SCH magnets. The effect from quench was evaluated and showed that the hot spot temperature was still at an acceptable level [10]. The inclusion of segregated, high purity copper strands reduces the impact.…”
Section: Reaction Heat Treatmentmentioning
confidence: 99%
“…A structural analysis for the three cases normal operation, quench and fault of resistive insert coil verified that the conductor stress levels stay well below the limits [16]. The fabrication of the superconducting cable-in-conduit coil and the cold-mass assembly was completed at the National High Magnetic Field Laboratory (NHMFL), Tallahassee, USA at the end of 2013 [17], [18]. Finally the cold mass was transported to Europe for further assembly into the magnet cryostat together with a pair of 20 kA current leads [19].…”
Section: A Series-connected Hybrid Magnetmentioning
confidence: 99%